Mathematical background design artificial of dentition in complete dentures - D. V. Lola; E. A. Bragin; Y. N. Maiboroda (Кубанский научный медицинский вестник)
The article is devoted to development of a mathematical model construction of dentition in complete dentures, based on the median between alveolar lines and angles for posterior teeth relative to the total alveolar arc. Get digital values of the standard deviation between alveolar lines for different types of atrophy of the alveolar ridges of edentulous jaws.